The Role of Information Awareness in Establishing Information Technology Infrastructure: An investigation of the opinions of Managers in a Sample of Business Organizations in Duhok - Ismael, Hadi K.; Saleh, Khoshman M. (Humanities Journal of University of Zakho, 2017)
The study aims at revealing the nature of the relationship between the information Awareness (the independent variable) and information technology infrastructures (the dependent variable). A number of hypotheses were formulated to determine the existence of a significant positive correlation between information literacy and information technology infrastructure as well as the significant impact relationship between them. Fifty nine business organizations that are operating in the city of Dohuk were selected practical part of the study, and a questionnaire form was administrated to the managers of these organizations and their assistants. The number of participants the study sample included one hundred individuals. The statistical hypotheses were tested using statistical methods and the results were analyzed using the statistical program (SPSS). The study found good levels of information literacy among the investigated organizations managements, and those good levels of information technology infrastructure requirements are in place in the investigated organizations .The study also found a direct significant correlation between information literacy and information technology infrastructure and also found an impact of information literacy on information technology in the investigated organizations. The study presented number of recommendations including the need of the organization's mission statement to include deployment of information literacy and its application among employees and the need to exploit and invest in the developments the physical components of the information technology infrastructure which allows utilizing them better.